Overcoming Regulatory Hurdles in the Indonesian Crowdfunding Landscape - Noor, Afif; Marzuki, Ismail; Saputro, Edy; Habib, Muhammad Akmal (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
With the exponential rise in crowdfunding, several pertinent issues have come to the fore. These include unauthorized access to personal data, exorbitant interest rates for funding recipients, and investor fund security concerns. Other issues, such as aggressive debt collection practices and misuse of donated funds, also warrant attention. The underdeveloped state of crowdfunding regulations in Indonesia, which offers insufficient legal certainty and protection, is often blamed for these issues. Thus, a thorough examination of the legal and regulatory framework governing crowdfunding in Indonesia is crucial. This study scrutinizes the legal norms, identifies, and harmonizes the diverse regulations applicable to crowdfunding in Indonesia. The findings underscore the necessity for enhancements in the laws and regulations pertinent to crowdfunding. Key areas of focus should include establishing a legal status for crowdfunding platforms, setting fair interest rates, fortifying investor fund security mechanisms, penalizing illegal crowdfunding activities, and intensifying oversight of fund usage in donation-based crowdfunding schemes. Equally crucial is the imposition of penalties for regulatory breaches in crowdfunding, reflecting a genuine commitment towards ensuring justice and legal certainty in all crowdfunding transactions.